Ethical principles in the use of Artificial Intelligence in the financial sector from a European perspective - Carmen Parra Rodriguez (Studia Prawnicze KUL, 2022)
Artificial intelligence (AI) has become part of our daily lives and is a fundamental tool for developing private and professional operations. In this sense, one of the sectors where AI has had the greatest impact has been the financial sector, where it is necessary to establish a regulatory framework to address two fundamental issues to ensure its proper functioning, specifically those aspects that affect digital transparency and neutral algorithms.